(untitled) - Kahn, Si (Silver Spring, Md., 1991)
"An NASW Press grassroots leadership book."; Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Community leadership; Community organization; Community power; Lãnh đạo cộng đồng; Tổ chức cộng đồng